2019
DOI: 10.7150/jca.28428
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA SNHG16 Promotes Hepatocellular Carcinoma Proliferation, Migration and Invasion by Regulating miR-186 Expression

Abstract: Long non-coding RNA (lncRNA) and microRNA (miRNA) play an important role in genesis and progression of tumors. The aim of this study was to explore the expression, biological function and molecular mechanism of small nucleolar RNA host gene 16 (SNHG16) in HCC. RT-qPCR was conducted to evaluate the expression level of SNHG16 in HCC tissues and cell lines. Our findings showed for the first time that SNHG16 was up-regulated in HCC tissues and cell lines. The expression of SNHG16 in cancer tissues was highly corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 27 publications
(34 reference statements)
2
52
0
Order By: Relevance
“…Results showed that SNHG16, SNHG17 and THAP9-AS1 were up-regulated in the high-risk group of NPC, while ZNF667-AS1 was down-regulated in the high-risk group of NPC. SNHG16 was regarded as an oncogene and associated with neuroblastoma, bladder cancer, colorectal cancer, esophageal squamous cell carcinoma, hepatocellular carcinoma [50][51][52]. Zhang et al suggested that SNHG16 promotes tumor progression through acting as an endogenous "sponge" by competing with miR-140-5p, thereby regulating target ZEB1 [51].…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that SNHG16, SNHG17 and THAP9-AS1 were up-regulated in the high-risk group of NPC, while ZNF667-AS1 was down-regulated in the high-risk group of NPC. SNHG16 was regarded as an oncogene and associated with neuroblastoma, bladder cancer, colorectal cancer, esophageal squamous cell carcinoma, hepatocellular carcinoma [50][51][52]. Zhang et al suggested that SNHG16 promotes tumor progression through acting as an endogenous "sponge" by competing with miR-140-5p, thereby regulating target ZEB1 [51].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that SNHG16 expression is significantly upregulated in tumor tissues and cell lines, such as hepatocellular carcinoma (HCC), lung cancer (LC), colorectal cancer (CRC) and glioma. 15,17,30,31 In addition, overexpression of SNHG16 indicates poor prognosis and is usually correlated with tumor size, lymph node metastasis, tumor grade, disease-free survival, and overall survival (OS). For example, to gain more in-depth knowledge of tumor biology, nine co-expression modules were identified in the Cancer Genome Atlas database after screening and analysis.…”
Section: Overexpression Of Snhg16 and Clinical Significance In Cancermentioning
confidence: 99%
“…15,[18][19][20][21][22][23] Further analysis showed that high expression of SNHG16 is associated with high tumor grade, multiple tumors, macrovascular invasion, large tumor size, and lymph node status, as well as poor diseasefree survival and shorter overall survival. 15,[19][20][21]23 In HCC patients, multivariate analysis identified SNHG16 overexpression as a significant independent predictor of poor prognosis. 20,23 Moreover, there are other studies of SNHG16 and related clinical effects in non-small cell lung cancer (NSCLC), osteosarcoma, glioma, bladder cancer (BC), ovarian cancer (OC), pancreatic cancer (PC), and papillary thyroid cancer (PTC).…”
Section: Overexpression Of Snhg16 and Clinical Significance In Cancermentioning
confidence: 99%
See 2 more Smart Citations